2002
DOI: 10.1074/jbc.m204202200
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Protein Transduction Is Cell Type-dependent and Is Enhanced by Dextran Sulfate

Abstract: Protein transduction domains (PTDs), both naturally occurring and synthetic, have been increasingly utilized to deliver biologically active agents to a variety of cell types in vitro and in vivo. We report that in addition to previously characterized arginine-rich PTDs, including TAT, lysine homopolymers were able to mediate transduction of a wide variety of cell types, as measured by flow cytometric and enzymatic assays. The efficiency of PTD-mediated transduction was influenced by the cell type tested, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 60 publications
8
124
1
Order By: Relevance
“…Early mechanistic studies on the cellular entry of PTDs were performed with fixed cells (11,13,(22)(23)(24)(25)(26)(27)(28). Fixation is believed to permeate membranes (30), and allows vesicle-entrapped peptides and proteins to travel to new locations (29,30,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early mechanistic studies on the cellular entry of PTDs were performed with fixed cells (11,13,(22)(23)(24)(25)(26)(27)(28). Fixation is believed to permeate membranes (30), and allows vesicle-entrapped peptides and proteins to travel to new locations (29,30,32).…”
Section: Discussionmentioning
confidence: 99%
“…Internalization was found to be energy-dependent, and the internalized peptide was observed in the endocytic vesicles of living cells (30). Dervan, Johansson, and their coworkers have reported similar cell-fixation artifacts for the transduction of N-methylpyrrole/Nmethylimidazole polyamides (31) and PTD-green fluorescent protein fusions (32).There have also been conflicting reports on whether PTDs bind to cell-surface glycosaminoglycans (GAGs) (11,27,33,34). The cell surface is coated with polysaccharides such as HS and sialic acid, and these molecules are known to mediate the binding of many proteins to cells (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein transduction technology based on small domains called protein transduction domains (PTDs) and cell penetrating peptides (CPPs) has been used to deliver exogenous protein into cultured cells and animal models (2)(3)(4)(5)(6)(7). Many research groups have demonstrated the efficacy of protein transduction technology for protein therapy strategies as well as drug delivery, although the exact mechanism of transduction remains unclear (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although various proteins have been developed for protein therapy, protein transduction technology has several limitations such as transduction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] However, the PTD-mediated uptake, which is initiated by ionic interactions with the cell surface, still requires high protein concentrations. 24,[27][28][29][30][31] As this limits the stimulation of T cells by PTD-coupled proteins in vivo, more efficient delivery systems are desirable.…”
Section: Introductionmentioning
confidence: 99%